Pengaruh Pembiayaan, NPF & FDR Terhadap Tingkat Profitabilitas Bank Kaltimtara Syariah Di Kota Samarinda - Mahmud Al Chusairi (FEB Universitas Maritim Semarang, 2022)
Financing is the main function and product of Islamic banking, namely the distribution of funds aimed at helping those in need, and if managed properly, can contribute significantly to Islamic banking income. However, in their distribution, funds carry many risks due to the uncertain and diverse nature of humans. This risk is reflected in the existence of loans that face problems that reduce the profits or profitability of Islamic banks. The purpose of this study is to explain the effect of Financing, Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on the profitability (ROA) of Bank Kaltimtara Syariah By including Financing, Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) as the independent variable and profitability (ROA) as the dependent variable. This is a quantitative research with multiple linear regression analysis techniques. The population or research theme is the annual report of Bank Kaltimtara Syariah. A total of 9 samples were taken from the Bank Kaltimtara Syariah Quarterly Financial Report for the 2016-2018 period. Based on the test results, it is known that tcount = - 1.4 98 < t table = 1.8 3 3 Financing and NonPerforming Financing (NPF) both have no significant positive effect on Return On Assets (ROA). While the Financing to deposit Ratio (FDR) regression shows a significant influence on Profitability (ROA). The amount of tcount is 1.859 > ttable 1.833